2019
DOI: 10.1016/j.ebiom.2019.05.035
|View full text |Cite
|
Sign up to set email alerts
|

The BET inhibitor JQ1 attenuates double-strand break repair and sensitizes models of pancreatic ductal adenocarcinoma to PARP inhibitors

Abstract: Background DNA repair deficiency accumulates DNA damage and sensitizes tumor cells to PARP inhibitors (PARPi). Based on our observation that the BET inhibitor JQ1 increases levels of DNA damage, we evaluated the efficacy of JQ1 + the PARPi olaparib in preclinical models of pancreatic ductal adenocarcinoma (PDAC). We also addressed the mechanism by which JQ1 increased DNA damage. Methods The effect of JQ1 + olaparib on in vivo tumor growth was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
79
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(94 citation statements)
references
References 47 publications
7
79
0
Order By: Relevance
“…In HR‐deficient head and neck cancers, Olaparib enhanced the radiotherapeutic ratio via disabling DNA replication processes . Moreover, recent studies have been focused on the combination of Olaparib with chemotherapeutic agents in cancer treatment . These combinations offer the prospect to broaden the clinical benefit of Olaparib beyond its use as monotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In HR‐deficient head and neck cancers, Olaparib enhanced the radiotherapeutic ratio via disabling DNA replication processes . Moreover, recent studies have been focused on the combination of Olaparib with chemotherapeutic agents in cancer treatment . These combinations offer the prospect to broaden the clinical benefit of Olaparib beyond its use as monotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…31 Moreover, recent studies have been focused on the combination of Olaparib with chemotherapeutic agents in cancer treatment. 32,33 These combinations offer the prospect to broaden the clinical benefit of Olaparib beyond its use as monotherapy. Although we have demonstrated the radiosensitization by Olaparib in radioresistant FaDu cells, the comprehensive mechanism remains a challengeable topic for future research.…”
Section: Radiosensitivity Is Typically Affected By Various Factors Inmentioning
confidence: 99%
“…Recent data in pre-clinical studies revealed that BET inhibitors exert potential anti-tumor effects in non-small cell lung cancer cells [27], mixed-lineage leukemia gene-fused leukemia [28], and other solid tumors including pancreatic ductal adenocarcinoma [29], prostate cancer [30]. In several subtypes of breast cancer, BET inhibitors have been shown to display a strong anti-tumor effect.…”
Section: Discussionmentioning
confidence: 99%
“…Targeting epigenetic factors such as BET family members cause defects in DSB repair and might provide beneficial effects in combination with PARP inhibitors [98]. Preclinical studies using BET inhibitor and PARP inhibitor combination have shown the superior anti-tumor efficacy compared to either agent alone in various cancer types [99][100][101]. We speculate that BET inhibition might enhance the anti-tumor activity of PARP inhibitor in SCLC through interference with DNA damage response.…”
Section: Co-targeting the Rsr Pathway And The Dsb Repair Systemmentioning
confidence: 92%